KUALITAS PELAYANAN PEREKAMAN DATA E-KTP DI KANTOR KECAMATAN PURWONEGORO KABUPATEN BANJARNEGARA - Kusmarini, Ratna Wulan; Subowo, Ari; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2013)
In the era of regional autonomy, the service provided by services institutions must be able to meet the expectations of society. In addition, the services provided must also be qualified and satisfy the public. Public service as a focus discipline of Public Administration science remains interesting to observe because of the services provided government services institutions are still considered unsatisfactory. Office Sub-District Purwonegoro in Banjarnegara district as one of the demographic service agencies must be able to provide data recording of e-KTP is good and on schedule. Reality on the ground say there are indications of dissatisfaction on the quality of services that include dimensions : tangible, reliability, responsiveness, assurance, and empathy given Office Sub-District Purwonegoro.The purpose of this study was to determine the quality of service as well as assessing five dimensions of service quality of e-KTP data recording that includes tangible, reliability, responsiveness, assurance, and empathy. This study used quantitative descriptive type of research using SERVQUAL.The results of this study indicate that service quality of e-KTP data recording at the Office Sub-District Purwonegoro weighs the performance of services by 6839 so that the quality of these services in the category of good, but not satisfactory because SERVQUAL score obtained is -634. The weight of expectation of services is 7473 so it is very high category. In addition the level of compatibility between performance and expectations on service quality of e-KTP data recording at the Office Sub-District Purwonegoro is 91.52%, so the service performance data recording e-ID nearly meet respondents expectations of service quality of e-KTP recording data given.Based on the analysis of the Cartesian diagram, tangible dimension in the quadrant A so that it is the first priority in repair. The dimensions of reliability in the quadrant B. This means that the execution (performance) those dimensions are in line with community expectations. Next is the dimension of responsiveness and empathy in the C quadrant so that the need for improvements in low priority. Assurance dimension in the D quadrant because the dimension is considered not very important, but execution (performance) exceed people's expectations. Through this research is expected to improve and enhance the service quality of e-KTP data recording in the Office Sub-District Purwonegoro